2008
DOI: 10.4143/crt.2008.40.3.101
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Gemcitabine plus Cisplatin in Patients with Anthracycline- and Taxane- Pretreated Metastatic Breast Cancer

Abstract: Purpose: Metastatic breast cancer patients are usually exposed to taxane and anthracycline as neoadjuvant, adjuvant and palliative chemotherapeutic agents. This study was designed to determine the efficacy and safety of the use of a gemcitabine and cisplatin (GP) combination treatment in patients with metastatic breast cancer that were pretreated with anthracycline and taxane. Materials and Methods:We evaluated the use of a GP regimen (1,000 mg/m 2 gemcitabine administered on days 1 and 8 plus 60 mg/m 2 cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
5
10
0
Order By: Relevance
“…The commonly used agents include capecitabine, vinorelbine, gemcitabine, pegylated liposomal doxorubicin, irinotecan, and ixabepilone [17]. The current study confirms the previous reports that combination chemotherapy with gemcitabine and cisplatin [13,[18][19][20][21][22]. These discordant results may be due to the small patient numbers, the heterogeneous patient populations and differing selection criteria.…”
Section: Discussionsupporting
confidence: 85%
“…The commonly used agents include capecitabine, vinorelbine, gemcitabine, pegylated liposomal doxorubicin, irinotecan, and ixabepilone [17]. The current study confirms the previous reports that combination chemotherapy with gemcitabine and cisplatin [13,[18][19][20][21][22]. These discordant results may be due to the small patient numbers, the heterogeneous patient populations and differing selection criteria.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, P.S was the only significant prognostic factor for TTP; Kim et al 24 reported the same result.…”
Section: Resultssupporting
confidence: 71%
“…The difference in RR and OS observed among these studies, including this study, most likely reflect patient selection with good prognostic factors as longer disease free interval (DFI), higher percentage of patients who had one metastatic site, hormonal receptor positive and HER-2 negative. The lower RR in the study of Burch 23 and Kim et al 24 are due to the use of GP combination as a second line treatment for metastatic disease.…”
Section: Resultsmentioning
confidence: 82%
“…The median TTP varied between 3.2 and 7.7 months, and median OS ranged from 7.4 to 19.5 months. The major toxicities were myelosuppression, peripheral neuropathy and nausea/vomiting (table 4) [83,84,85,86,87,88,89,90,91,92]. In the study by Nagourney et al [83], 13% of patients had grade III/IV neutropenia, 6% had anemia, 31% had thrombocytopenia, 4% had nausea/vomiting and 2% had peripheral neuropathy.…”
Section: Experience With Combination Chemotherapymentioning
confidence: 99%
“…In the study by Nagourney et al [83], 13% of patients had grade III/IV neutropenia, 6% had anemia, 31% had thrombocytopenia, 4% had nausea/vomiting and 2% had peripheral neuropathy. Most studies observed that this regimen is well tolerated, with grade III/IV leukopenia and thrombocytopenia being the most serious adverse events and nonhematological toxicity rarely being severe [86,87,88,89,90,91,92]. …”
Section: Experience With Combination Chemotherapymentioning
confidence: 99%